ПЕДАГОГИКАЛЫҚ ҚАРЫМ-ҚАТНАС МӘДЕНИЯТЫ - Пазылов, А. (SCIENCE and SOCIETY, 2019)
The article is devoted to the issues of culture of pedagogical approach.
Keywords: Ethnopedagogics; pedagogical relation; hair; scissors; dean; student